Open water swimming in elite triathletes: physiological and biomechanical determinants - López-Belmonte, Ó.; Gay, A.; Ruiz-Navarro, J. J.; Cuenca-Fernández, F.; Cejuela, R.; Arellano, R. (International Journal of Sports Medicine, 2024)
This study aimed (i) to analyze the 1500 m open water swimming performance, (ii) to examine the associations between physiological and biomechanical variables with swimming performance, and (iii) to determine which variables can predict swimming performance in triathletes. Fourteen elite triathletes (23.4±3.8 y) performed a 1500 m test in open water swimming conditions. Swimming performance was assessed using World Aquatics Points Scoring, and data were obtained from the 1500 m open water swimming test. Heart rate, end-exercise oxygen uptake (EEO2) and blood lactate concentrations were measured. The initial 250 m of the 1500 m swimming test presented the highest values of biomechanical variables in males (i. e. swimming speed, stroke rate (SR), length (SL), index (SI)). A decrease in SL was observed in the last 250 m in both sexes. Positive association were found between EEVO2 (r=0.513; p=0.030), swimming speed (r=0.873; p<0.001) and SI (r=0.704; p=0.002) with swimming performance. In contrast, time constant of the oxygen uptake (r=-0.500; p=0.034) and buoy-turn times (r=-0.525; p=0.027) were negatively associated with performance. SI was the main predictor (R 2=0.495) of open water swimming performance in triathletes. In conclusion, triathletes and coaches must conduct open water training sessions to maximize SI (i. e. swimming efficiency).